2015
DOI: 10.1038/tp.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

In the face of threat: neural and endocrine correlates of impaired facial emotion recognition in cocaine dependence

Abstract: The ability to recognize facial expressions of emotion in others is a cornerstone of human interaction. Selective impairments in the recognition of facial expressions of fear have frequently been reported in chronic cocaine users, but the nature of these impairments remains poorly understood. We used the multivariate method of partial least squares and structural magnetic resonance imaging to identify gray matter brain networks that underlie facial affect processing in both cocaine-dependent (n=29) and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 100 publications
4
14
0
Order By: Relevance
“…Emotions have a critical role in the development, maintenance and successful treatment of addiction. 1 , 2 , 3 Suppression of negative affective states such as anxiety and withdrawal symptoms is one motivational pathway to support the consumption of alcohol. 4 , 5 As negatively reinforced drinking becomes more pronounced, negative affective states increase, thereby escalating alcohol intake and raising vulnerability to relapse after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Emotions have a critical role in the development, maintenance and successful treatment of addiction. 1 , 2 , 3 Suppression of negative affective states such as anxiety and withdrawal symptoms is one motivational pathway to support the consumption of alcohol. 4 , 5 As negatively reinforced drinking becomes more pronounced, negative affective states increase, thereby escalating alcohol intake and raising vulnerability to relapse after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies with cocaine and methamphetamine users have revealed that their ability to identify basic facial affect expressions is largely unimpaired (108)(109)(110)(111)(112)(113)(114). However, a few studies have found specific alterations in fear (115)(116)(117)(118) and anger processing (115) from faces in regular users of cocaine or methamphetamine. Moreover, in polysubstance users, fear and anger recognition performance was negatively correlated with cocaine use intensity (119), while another study did not show an effect of stimulant polysubstance use on facets of cognitive empathy when assessed with complex stimuli (120).…”
Section: Stimulants Emotion Recognition and Cognitive Empathymentioning
confidence: 99%
“…; Morgan & Marshall ; Ersche et al . ). Another study found decreased emotion recognition in cocaine users due to lowered identification of emotion from vocal prosody and difficulty integrating cross‐modal (prosody/facial) affective information.…”
Section: Introductionmentioning
confidence: 97%
“…; Morgan & Marshall ; Ersche et al . ), two recent studies examined social reward processing, a key dimension of social motivation. In one, cocaine users showed blunted social reward during virtual interaction relative to controls, indicated by self‐report and physiological measures.…”
Section: Introductionmentioning
confidence: 99%